Enhancing Pediatric Education for Physical Therapy Students Through the Development of Community Partnerships to Facilitate Experiential Learning: A Case Report. Issue 3 (September 2019) - Wolden, Mitch; Anderson, Brittany
Abstract : Background and Purpose: Doctoral physical therapy (DPT) programs are expected to provide students with educational experiences in classroom and in clinical settings and with all age demographics, including pediatrics. There is significant discrepancy in the delivery and assessment of pediatric content in DPT programs. One effective and evidence-based strategy to address this discrepancy and deliver pediatric content is experiential learning (EL). Our case report illustrates how EL with a symbiotic community partner can enable DPT programs to effectively address the current limitations in direct contact hours and clinical experiences in pediatrics. Case Description: We formed a structured and formal partnership with a local community fitness and gymnastics facility to provide our students with pediatric EL opportunities outside of the classroom and traditional clinic settings. Each student is required to engage in structured and focused play-based interactions with typically and atypically developing children 1 hour per week for two 8-week EL periods under direct supervision of a certified pediatric clinical specialist. Outcomes: Students demonstrated appropriate professional behaviors, increased self-efficacy, achievement of the pediatric course learning objectives, and attainment of 3 Academy of Pediatric Physical Therapy essential core competencies. With our community partner, 87% of the children demonstrated improvement in their gross motor skills. Discussion and Conclusion: Our case report details an innovative approach to use EL to increase the number of direct contact hours with the pediatric population through a symbiotic community partnerships that positions our students to reach entry-level competency with the pediatric population upon graduation. Abstract : Supplemental Digital Content is Available in the Text.